Biopolymer-solid lipid hybrid microparticles as a nutraceutical co-delivery carrier in the gastrointestinal tract - Ho, Chin Guan (2017)
Many obstacles are faced during oral delivery, for example, low bioavailability, multiple dosing, and side effects in the gastrointestinal tract. Two types of drug delivery systems are studied to address these problems of nutraceutical and drug delivery in the gastrointestinal tract. Firstly, a combination of water-in-oil-in-water (W/O/W) double emulsion and hot emulsification fabrication techniques are employed to design a novel alginate-solid lipid hybrid microparticles (SLM) to co-encapsulate two bioactive compounds, riboflavin and quercetin. Secondly, acarbose is reformulated into alginate-PLGA hybrid core-shell microparticles to investigate the release kinetics of acarbose in a simulated gastrointestinal tract for oral administration. In SLMs, riboflavin and quercetin are shown to localize in different carrier materials, with the encapsulation efficiency up to 50 % and 89 %, respectively. The release profiles show complete release within 24 hours except for Compritol 888 Ato. However, Compritol with the incorporation of liquid lipid can achieve the total release of 90%, which proves the potential for the Compritol formulation to be used in oral delivery. Now, the SLMs exhibit similar release kinetics for two bioactive compounds according to Higuchi’s equation, and anomalous transport in power’s law. Release profile and release kinetics suggest that SLM can successfully co-encapsulate and co-deliver two bioactive compounds despite their hydrophilicity. In the second part of the project, the uncoated alginate-PLGA hybrid microparticles exhibit sustained-release of acarbose up to 24 h, whereas commercial tablet Glucobay® exhibits fast release in less than 5 mins. Hybrid microparticles coated with polyelectrolytes can further retard the release in simulated gastric fluid from 70% to 35%. Both coated and uncoated formulations can be best-fitted into power’s law. From the fitted data, the uncoated formulation exhibits anomalous transport, however, the release exponent change to Case II transport for coated formulation due to the effect of the additional coating layer. In a nutshell, both studies provide evidence that the novel hybrid SLM and modified polymeric system are promising oral delivery systems to suit different needs for nutraceutical and drug delivery in the gastrointestinal tract.